The history and development of the theory and practice of cybercartography - Taylor, D.R. (Fraser); Pyne, S. (Stephanie) (International Journal of Digital Earth, 2010)
This paper describes the development of cybercartography since the introduction of the term in 1997. Although the origins of cybercartography were largely conceptual in nature, the evolution of cybercartography to date has been an iterative process reflecting the creative interplay between theory and practice. A major step forward was made in 2002 when the Geomatics and Cartographic Research Centre at Carleton University received a $2.5 million grant from the Social Sciences and Humanities Research Council of Canada to explore the utility of cybercartography to what was described as the New Economy. By 2006, the interaction between theory and practice had led to considerable advances in cybercartography as a holistic, location-based concept and two new cybercartographic products, the Cybercartographic Atlas of Antarctica and the Cybercartographic Atlas of Canada's Trade with the World, were produced. Between 2006 and 2009, cybercartography was further developed as a result of interaction with indigenous communities, especially in Canada's north and new interactive atlases such as the Kitikmeot Place Names Atlas and the Community Atlas of Arctic Bay were created in coope